Children first : the story of UNICEF, past and present - Black, Maggie (Oxford ; New York : Oxford University Press, 1996)
Celebrating 50 years of UNICEF - one of the chief organisations working for children - this book is a celebration and an exploration of how recent changes in public attitudes and government policy have put children at the top of the agenda.
Includes bibliographical references and index.
Keywords: Child welfare -- History; Child welfare -- History; Child welfare -- History -- Developing countries